Esophageal cancer in elderly patients: a population-based study - Zeng, Yuan; Liang, Wenhua; Liu, Jun; He, Jiaxi; Ng, Calvin S. H.; Liu, Chia-Chuan; Petersen, René Horsleben; Rocco, Gaetano; D’Amico, Thomas; Brunelli, Alessandro; Chen, Haiquan; Zhi, Xiuyi; et al. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: As the aging issue and increased elderly esophageal cancer (EC) patients, we sought to study the clinical characteristics, treatment modality and outcomes of EC patients 70 years or older compared with those younger than 70 years old. Methods: The national surveillance, epidemiology, and end results (SEER) database for the period from 1973 to 2013 was analyzed. The patient and treatment characteristics were compared between the age groups. Multivariate Cox proportional hazard regression analyses were also performed to identify independent prognostic factors. Propensity-score matching analyses (PSA) regarding survival after different treatments were also performed in locoregional EC. Results: Compared with the younger group, patients 70 years or older were characterized by having a higher proportion of patients with female gender, white race, localized disease, non-adenocarcinoma and without any treatment, as well as inferior overall survival (OS) [hazard ratio (HR), 1.324] and EC-specific survival (HR, 1.270). In addition, older patients shared same independent prognostic factors with younger patients, including age, histology and race. Specifically, compared with those receiving no intensive treatments, surgery alone (HR, 0.342), both surgery and RT (HR, 0.323) and RT only (HR, 0.525) were favorable among elderly patients, as confirmed by both multivariate adjustment and PSA. Conclusions: Compared to younger EC patients, those 70 years or older showed distinctive clinical characteristics and inferior survival. Despite showing a higher proportion of localized disease, patients 70 years or older were less likely to be subjected to surgery or/and RT. Thus, the role of intensive treatments, which were identified as favorable factors among elderly patients in this study, warrants further investigation.